PEMBERDAYAAN WALI MURID TK DALAM EDUKASI PMT MELALUI MEDIA EDUKASI DI DESA DUKUHTENGAH KECAMATAN KRIAN SIDOARJO - Suliati, Suliati; Museyaroh, Museyaroh; Yunita, Era Fitria; Istanto, Wisnu (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2025)
Stunting is still a big problem in Indonesia because it affects how kids grow and develop over time, especially if it isn't stopped early on. One reason for this is that parents, especially mothers, don't fully understand how to provide balanced nutritional supplementary feeding (PMT). This community service project is all about giving the guardians of Dharma Wanita Persatuan Kindergarten in Dukuhtengah the tools and information they need to do their jobs better. It will do this by making and using interactive educational media in Dukuhtengah Village, Buduran District, Sidoarjo Regency. The implementation method has many steps: working with the school, finding out what parents need to know, making educational materials like booklets and posters, giving advice and showing how to prepare PMT, and testing the students before and after. In total, 36 parents took part in this activity. The analysis results show that the participants' understanding has improved a lot. They scored an average of 54.86 on the pre-test and 86.39 on the post-test, which is an increase of 31.53 points. The paired t-test produced p<0.001, signifying a significant difference, and Cohen's d effect size of 3.79 indicates a substantial effect. This finding shows that the educational media that was created works to teach parents more about PMT and how to stop stunting. In conclusion, interactive educational empowerment activities that use media have been shown to help parents improve their ability to provide their children with the right extra food to meet their nutritional needs. The future goal is to repeat the activities at the Posyandu level and combine them with family-based public health programs to make stunting prevention more effective in the community. ABSTRAKStunting masih menjadi permasalahan serius di Indonesia karena berdampak pada tumbuh kembang anak jangka panjang, terutama bila tidak dicegah sejak dini. Salah satu faktor penyebabnya adalah kurang optimalnya pemahaman orang tua, khususnya ibu, mengenai pemberian makanan tambahan (PMT) bergizi seimbang. Kegiatan pengabdian kepada masyarakat ini berfokus pada pemberdayaan dan edukasi wali murid TK Dharma Wanita Persatuan Dukuhtengah melalui pembuatan dan penggunaan media edukasi interaktif di Desa Dukuhtengah, Kecamatan Buduran, Kabupaten Sidoarjo. Metode pelaksanaan mencakup beberapa tahapan, yaitu koordinasi dengan pihak sekolah, identifikasi kebutuhan pengetahuan wali murid, penyusunan media edukasi berupa booklet dan poster, penyuluhan serta demonstrasi penyajian PMT, serta evaluasi dengan pre-test dan post-test. Sebanyak 36 wali murid berpartisipasi aktif dalam kegiatan ini. Hasil analisis menunjukkan adanya peningkatan signifikan pada pemahaman peserta, dengan rata-rata skor pre-test sebesar 54,86 dan post-test sebesar 86,39, sehingga terjadi peningkatan sebesar 31,53 poin. Uji t berpasangan menghasilkan p<0,001 yang menandakan perbedaan signifikan, sementara nilai effect size Cohen’s d sebesar 3,79 menunjukkan efek yang sangat besar. Temuan ini mengindikasikan bahwa media edukasi yang dikembangkan efektif dalam meningkatkan pengetahuan wali murid mengenai PMT dan pencegahan stunting. Kesimpulannya, kegiatan pemberdayaan berbasis media edukasi interaktif terbukti mampu meningkatkan kapasitas orang tua dalam memberikan PMT yang sesuai kebutuhan gizi anak. Prospek ke depan adalah replikasi kegiatan pada jenjang Posyandu, serta integrasi dengan program kesehatan masyarakat berbasis keluarga untuk memperluas dampak pencegahan stunting di tingkat komunitas..